ICT and the dual banking efficiency nexus: A cross-country analysis with country governance moderation in GCC countries - Heng, Luo; Kamarudin, Fakarudin; Mohd Nor, Normaziah (Cogent OA, 2023)
Our study investigates the influence of information and communication technology (ICT) applications at the national level on the efficiency of Islamic banks (IBs) and conventional banks (CBs) operating in Gulf Cooperation Council (GCC) countries. We analyze data collected from both CBs and IBs in GCC countries over the period spanning from 2006 to 2021. Specifically, ICT in this context refers to the extent to which ICT is applied on a national scale, encompassing activities both within and outside the banking sector. In our basic regression, we observe that ICT negatively impacts both types of bank efficiency, with the effect varying depending on the type of bank. Notably, the coefficient of IBs is slightly higher than that of CBs. Country governance (GC) moderates the negative effect of ICT on both types of bank efficiency. Additional robustness